Life narratives of peolple with chronic kidney insufficiency: self-care and coping mechanism (Research, Society and Development, 2020)
Chronic Kidney Disease is characterized by a progressive and irreversible loss of the kidney's glomerular, tubular and endocrine function. Considered one of the most serious of all chronic diseases due to injuries, physical and psychological damage and consequences for people's daily lives, influencing their self-care.Objectives: To identify in the life narratives of people undergoing conservative treatment of chronic renal failure how the diagnosis was discovered; and how they project their needs for self-care and coping mechanisms. Method: Descriptive, qualitative and Life Narrative, based on the theoretical framework of Nola Pender. Convenience sample including 14 people with chronic kidney disease, at a university institution. Open interview with thematic analysis. Results: Different experiences were evidenced in relation to the discovery of Renal Insufficiency Chronic, with the need for changes in the way of life. The coping mechanisms arose from changes in diet supported by family and religious belief. Final considerations: The discovery of the illness occurred at random, associated with other pathologies or signs and symptoms. The whole process of illness was marked by pain, suffering in different ways, distrust of the diagnosis and denial of the disease. As for projecting their needs for self-care and coping mechanisms, the results showed the urgency of a more human service, given the difficulty of access, waiting time and the search for care. The nurse is essential in creative practices to influence Health Promotion, helping to reframe negative experiences and favoring the reinsertion of these individuals in the society in which they live.